Антропозооморфні шаманські пряжки перехідного періоду від середньої до пізньої бронзи - Отрощенко, В.В. (Археологія, 2019)
Йдеться про дискусію з приводу походження та семантики антропозооморфних фігурних пряжок перехідного періоду від середньої до пізньої бронзи півдня Східної
Європи. Автор зосереджує особливу увагу на семантиці
фігурних пряжок Дніпро-Донської Бабинської та Лолінської культур, зв’язку аналізованих артефактів із виконанням небіжчиками шаманських практик. Залучено
синхронні артефакти лісових культур Східноєвропейської рівнини та етнографічний фактаж сибірського
шаманства. Статья посвящена дискуссии c Р. А. Мимоходом по поводу генезиса и семантики антропозооморфных фигурных пряжек переходного периода от средней к поздней бронзе юга Восточной Европы, выявленных в погребениях. Автор сосредоточил особое внимание на семантике фигурных пряжек Днепро-Донской Бабинской
(ДДБК) и Лолинской культур. Он доказывает, что фигурные пряжки являются антропозооморфными, а не антропоморфными, как считает Р. А. Мимоход. Обращено внимание на маскоидном характере фигурных пряжек
Лолинской культуры. Это связывает подобные артефакты с выполнением умершими шаманских практик при
жизни. Специфика фигурных пряжек ДДБК заключается в соединении безголового торса человека с зооморфным постаментом-букранием. Две пряжки этого типа найдены в Шагарском могильнике Озерного Мещерья (Рязанская область, РФ). Торс одного из них был увенчан резной птичьей головкой. Автор допускает, что бронзовые
идолы с Галичского клада шамана (Костромская область, РФ) выполняли функцию пряжек — элемента шаманского убранства. Привлечены аналогии из практики сибирского шаманства. Проявления шаманизма по линии
Сейма-Турбино (Галичский клад) — Шагара — Лола — ДДБК вписывается в раннюю фазу переходного периода
от средней к поздней бронзы (ХХІІ—ХХ вв. до н. э.). Такой вывод подкреплен калиброванными радиоуглеродными датами соответствующих комплексов. В целом же группа фигурных пряжек ДДБК достаточно гомогенна.
Определяя их семантику стоит учитывать преемственность обрядовых и идеологических традиций Трипольской
и Ямной общностей, реагируя на определенный «ямный ренессанс» в переходный период от средней к поздней
бронзе. Изложенный в статье альтернативный взгляд на семантику фигурных пряжек ДДБК и Лолы ни коим
образом не приуменьшает ценность интересных наблюдений, приведенных аналогий и выводов дискуссионной
статьи Р. А. Мимохода The article is dedicated to discussions with R. O. Mymokhod on the issue connected with the genesis and semantics of
anthropozoomorphic figured buckles of the transitional period from the Middle to the Late Bronze Age of southern Europe
thatwere discovered inburials.The authorfocuses onthe semantics offigured buckles oftheDnieper-DonBabynska (DDBC)
and Lolinska archaeological cultures. He argues that these buckles are anthropozoomorphic, and not anthropomorphic, as
R. O. Mymokhod considers. The attention is paid to the maskoid character of Lolinska culture figured buckles, which links
these artifacts to the performance of shamanic practices by the deceased. The specificity of the DDBC figured buckles is in
the combination of a headless torso of a human with zoomorphic pedestal-bucranium. Two buckles of this type were found
in the Shagar burial ground of Meshchyora lakes (Riazan region, the Russian Federation). The torso of one of them was
decorated with a carved bird’s head. The author proves that bronze idols from the Galich shaman treasure (Kostromskaya
region, the Russian Federation) were used as buckles — an element of shamanic clothing. Analogies have been drawn from
the practice of Siberian shamanism. The author points out that the manifestations of shamanism along the Seim-Turbino
(Galich treasure) — Shagara — Lola — DDBC belong to the early phase of the transitional period from the Middle to the
Late Bronze Age (XXII—XX c. BC).
Such a conclusion is supported by the calibrated radiocarbon dating of the corresponding complexes. In general, the
group of figured DDBC buckles is sufficiently homogeneous, and while determining their semantics it is necessary to take
into account the heredity of ceremonial and ideological traditions of Trypillia and Yamna communities, considering a
certain “Yamna culture renaissance” during the transitional period from the Middle to the Late Bronze Age. The alternative
view of the DDBC and Lola cultures buckles semantics does not in any way diminish the value of interesting observations,
the analogies listed, and the conclusions of the R. O. Mymokhod article under disscussion.